Termination of the contract without notification of the employee - Ziółkowska, Krystyna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article considers the grounds for termination of the employment contract without notifying the employees of the pipeline. The contractual employment relationship may be terminated by termination at the will of the parties or one of the parties as a result of the relevant legal act that performs them, or termination by law, regardless of the will of the parties. Based on Art. 30 p. 1 pp. 1-3 of the Labor Code, contractual employment may be terminated by performing one of the following legal actions committed by one of the parties to the employment relationship: agreement to terminate the employment contract, termination of employment contract and termination without notice. It is also emphasized that an employment contract concluded for a probationary period or for a definite period is terminated after the end of the period for which it was concluded.The employer's actions aimed at discrediting and harming the employee's personal rights in response to the permitted and constructive criticism of the director of the workplace against the unfavorable decisions of the founding body or the owner may be qualified as a serious breach of the employee's basic obligations. employment contract without notice through the fault of the employer. Other obligations that the employer may violate in relation to the employee are: the obligation to ensure safe and hygienic working conditions, all obligations related to social insurance, obligations related to the principles of social coexistence.